(untitled) (Journal of the College of Basic Education, 2023)
This study aims to highlight the importance of one of the most important modern educational tools, which is known as “conceptual maps” and focus on its effectiveness and efficiency in facilitating the teaching of the Arabic language. In the grammatical concepts and the interconnections and relationships that the individual experienced and kept in his brain (the previous experience), as great importance relies on linking the new grammatical concepts to the existing conceptual structure of the student. These conceptual structures are the first factor that judges whether the new grammatical concepts will be meaningful. In order to learn, and from this standpoint, Arabic language teachers in particular must choose modern teaching methods that help students enrich their information, develop their different mental skills, and provide them with sound thinking methods, which leads to raising the level of their conceptual structure and making it more coherent. Perhaps one of the most prominent modern methods that appeared in The recent use of conceptual maps in teaching, because of their great importance in creating meaningful learning, increasing the level of achievement, and making For a student who.